Sparse Approximation of Images Inspired from the Functional Architecture of the Primary Visual Areas. (28th December 2006) - Fischer Fischer, Sylvain Sylvain; Redondo Redondo, Rafael Rafael; Perrinet Perrinet, Laurent Laurent; Cristóbal Cristóbal, Gabriel Gabriel
Abstract : Several drawbacks of critically sampled wavelets can be solved by overcomplete multiresolution transforms and sparse approximation algorithms. Facing the difficulty to optimize such nonorthogonal and nonlinear transforms, we implement a sparse approximation scheme inspired from the functional architecture of the primary visual cortex. The scheme models simple and complex cell receptive fields through log-Gabor wavelets. The model also incorporates inhibition and facilitation interactions between neighboring cells. Functionally these interactions allow to extract edges and ridges, providing an edge-based approximation of the visual information. The edge coefficients are shown sufficient for closely reconstructing the images, while contour representations by means of chains of edges reduce the information redundancy for approaching image compression. Additionally, the ability to segregate the edges from the noise is employed for image restoration.